River pollution relationship to the national health indicated by under-five child mortality rate: a case study in Malaysia - Abdul Wahab, Mohd Aqmin; Jamadon, Nur Khaliesah; Mohmood, Adzleen; Amir Hamzah, Amir Syahir (Hibiscus Publisher, 2015)
The trend of global under-five child mortality rate showed a steady decrease at -3.14% per year approaching the United Nations millennium development goals target (-4.0% reduction per year from 1990-2015). This rate is usually inversely proportional to the nations GDP. However, the progress in the recent years (2006-2012) in Malaysia has raised a disturbing concern with an annual average increment of +0.81% per year. Thus, there is an urgent need to identify the reasons of such risky ecosystem. By analyzing recorded data on river pollution from 2007-2012, we found that river pollution has high correlation with the gross domestic products, not at the same year, but for two years prior that indicates a lag time. We also found that under-five child mortality has strong correlation with the river pollutions. The development-pollution health triangular cycle needs to be put in a balanced to ensure the nation prosperity and sustainability of the nation.